Complementary leaflet for the study of the basic course of brain-cardiopulmonary resuscitation in Medicine Studies - José Alejandro Lagar Álvarez; Daniela de la Caridad Piloto Porras; Raidel González Rodríguez; Juan Cardentey García (Universidad Médica Pinareña, 2019)
Introduction: the course of basic brain-cardiopulmonary resuscitation is included in the curricular design of the undergraduate degree in Medicine, confirming the need to strengthen the learning process in students through the establishment of didactic materials.